Baltic Barometer 2021. 30 Years after the fall of the Soviet Union (Public opinion data: representative samples of the adult population in Estonia, Latvia and Lithuania) - Ekman, Joakim; Duvold, Kjetil; Berglund, Sten (Södertörn University, 2023)
Representative samples of populations in Estonia, Latvia and Lithuania.
This is our follow-up survey (from 2014) in the three Baltic countries but without additional sampling of their respective Russian speaking minorities. Special focus is on the handling of the covid pandemic in the Baltic countries, but the survey also covers attitudes towards the EU, migration, democracy, and Russia against the backdrop of its aggression in Ukraine.

Representativa urval av befolkningen i Estland, Lettland och Litauen.
Detta är vår uppföljande undersökning (från 2014) i de tre baltiska länderna, men denna gång utan ytterligare urval från de rysktalande minoriteterna i respektive land. Särskilt fokus ligger på hanteringen av covid-pandemin i de baltiska länderna, men undersökningen omfattar även attityder till EU, migration, demokrati samt Ryssland mot bakgrund av landets aggression i Ukraina.
Baltic Barometer 2021. 30 Years after the fall of the Soviet Union (Public opinion data: representative samples of the adult population in Estonia, Latvia and Lithuania)
Baltic Barometer 2021. 30 Years after the fall of the Soviet Union.
Keywords: PUBLIC OPINION; ALLMÄN OPINION; Political Science (Excluding Peace and Conflict Studies); Statsvetenskap (exklusive freds- och konfliktforskning)